Using deixis in sport articles - Alikulova , Shaxnoza (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
The purpose of this research is to identify deixis forms and meanings used in articles. This study was applied qualitative descriptive. Then, it was analyzed by using the Dylgjeri and Kazazi concept the data was table from in BBC sport article . The findings indicate that the types of deixis found in articles. The first person there are I, Me, My, We, and Our (In third person there are She, Her, His, Him, and They), deixis spatial (there are school, class, hospital, on the stairs, world, here and there.), and temporal deixis. (there are now, then, five month ago, today, and yesterday). The results of this study show that person deixis is used 63 times and have percentage 66.5% spatial deixis is used 8 times and have percentage 10.5% and temporal deixis is used 9 times and have percentage 22,8%